Emotional attentional capture in children with conduct problems: the role of callous-unemotional traits - Hodsoll, Sara; Lavie, Nilli; Viding, Essi (Frontiers in Human Neuroscience, 2014)
Objective: Appropriate reactivity to emotional facial expressions, even if these are seen whilst we are engaged in another activity, is critical for successful social interaction. Children with conduct problems and high levels of callous-unemotional traits are characterised by blunted reactivity to other people’s emotions, while children with conduct problems and low levels of callous-unemotional traits can over-react to perceived emotional threat. No study to date has compared children with conduct problems and high vs. low levels of callous-unemotional traits to typically developing children or each other, using a task that assesses attentional capture by irrelevant emotional faces. Method: All participants performed an attentional capture task in which they were asked to judge the orientation of a single male face that was displayed simultaneously with two female faces. Three types of trials were presented, trials with all neutral faces, trials with an emotional distractor face and trials with an emotional target face. 15 boys with conduct problems and high levels of callous-unemotional traits, 17 boys with conduct problems and low levels of callous-unemotional traits and 17 age and ability matched typically developing boys were included in the final study sample. Results: Compared to typically developing children and children with low levels of callous-unemotional traits, children with conduct problems and high levels of callous-unemotional traits showed reduced attentional capture by irrelevant emotional faces. Conclusions: This study is the first to demonstrate a different pattern in emotional attentional capture in children with conduct problems depending on their level of callous-unemotional traits.